Does Financial Ratios and Company Size Affect Dividend Payout Ratio? - Nuriatullah Nuriatullah (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
The purpose of this study was to determine whether the Loan to Deposit Ratio (LDR), Debt to Equity Ratio (DER), Growth, Return On Assets (ROA), and Firm Size have an effect on the Dividend Payout Ratio (DPR). The data used in this research is secondary data in the form of banking financial performance data, and is obtained from the Annual Financial Statements of Commercial Banks listed on the Indonesia Stock Exchange 2015-2018. Banking used is 30 companies with a total sample of 120. The data is pooled data. The data were analyzed by using the multiple linear regression method with the SPSS analysis tool. LDR has a significant positive effect on the DPR, DER has a significant negative effect on the DPR, Growth has a significant negative effect on the DPR, Return on Assets (ROA) has a significant positive effect on the DPR, Bank Size has a significant positive effect on the DPR. Overall, the independent variables together have a significant effect on the DPR.